The moral warrior : ethics and service in the U.S. military - Cook, Martin L., 1951- (SUNY series, ethics and the military profession., 2004)
For the first time in history, the capabilities of the U.S. military for outstrip those of any potential rival, either singly or collectively, and this reality raises fundamental questions about its role, nature, and conduct. The Moral Warrior explores a wide range of ethical issues regarding the nature and purpose of voluntary military service, the moral meaning of the unique military power of the United States in the contemporary world, and the moral challenges posed by the "war" on terrorism.